INNOVATION AND KNOWLEDGE MANAGEMENT IN BUSINESS GLOBALIZATION: THEORY & PRACTICE, VOLS 1 AND 2 - Yew-Siang, Poong; Uchenna Cyril, Eze (2008)
Drawing from the literature of innovation diffusion theory, human-computer interface and social behaviour theory, this paper proposes the Innovation Acceptance Model (IAM) to predict the factors influencing the adoption of new generation innovation. New generation innovations are ubiquitous, highly customisable and have expanded social network effect. IAM aims to predict innovations that are targeted for mass users and featuring innovation characteristic beliefs that are not accommodated by previous models of technology acceptance.